Analysis of the Reaction Kinetic of Pyrolysis Process in the Styrofoam Waste by using Catalyst Cu - Herdianto, Monek; Kholidah, Nurul; Mariyamah, Mariyamah (Walisongo Journal of Chemistry, 2023)
Styrofoam is one of the biggest contributors to plastic waste. Styrofoam includes polystyrene plastics derived from styrene monomers, which cannot decompose naturally. The method commonly used to process plastic waste is pyrolysis. The purpose of this study is to determine the effect of the number of Cu catalysts on the kinetics of the reaction in the Styrofoam waste pyrolysis process. Based on the research that has been done, the addition of cu catalysts affects the kinetics of the reaction in the pyrolysis process of styrofoam waste. The fastest rate of reaction is a catalyst of 8%, while for the slow rate, the catalyst is 0%. In the catalytic reaction, 10% of the reaction rate is decreased. This is due to the formation of lumps between the catalyst and the styrofoam that makes the catalytic reaction not work optimally.